O inventário do patrimônio arquitetônico das zonas de entorno dos bens tombados de Cruz Alta - RS - Moreira, Pedro Couto (2014)
The history and culture of a people can be known through its architectural heritage, since the urban landscape is a physical representation of the identity of the city and its inhabitants. Over time these forming components of a city are being undervalued or even overlooked, thus subject to degradation due to population unaware of its importance. The preservation of the buildings that make up part of forming the place can ensure the preservation of its history, helping to cultural elements are not lost over the years in addition to being an instrument for the government to determine their urban policies. The study about the built set of a place can become a tool for analysis and understanding of its chronological development. Based on this, the research aims to highlight the historic value, the importance of preserving and disseminating to society the architectural heritage of the city of Cruz Alta, between its founding in 1821 until the mid-1960s, being the date behaves singular buildings of modernist architecture inserted in surrounding areas of listed buildings, by performing an architectural inventory. Cruz Alta was part of the begin of colonization and development of the state of Rio Grande do Sul, having on your physical heritage, intangible meanings and symbolic representations, which refer to important moments and past tenses linked to personalities that have marked the history and culture of both the region as the nation. Chips from inventory of IPHAE were used to cataloging of buildings and the criterion for selection was beyond the time frame, the demarcation of surrounding zones of listed buildings, provided by municipal legislation, making the choice through its relevance Historical-Cultural and Morphological-Architectural. So 25 buildings were selected, recording their particulars, photographs, general information and technical analysis that accounted for the influences of Neoclassical, Eclectic, Neo Colonial, Art Deco and Modernist styles. From these information, it was made the Visual Guide to Historic Architecture of Cruz Alta, aimed at the dissemination and appreciation of heritage. In his closing, the research is pondering on the topic and outlines actions necessary for issues pertaining to heritage assets.